1993
DOI: 10.1042/bj2920303
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic control of induction of type II iodothyronine 5′-deiodinase activity in cultured mouse brown adipocytes

Abstract: Iodothyronine 5'-deiodinase (5'D) of mouse brown adipocytes differentiated in cell culture was characterized in detail with respect to the adrenergic control of its biosynthesis. The stimulation of 5'D required mRNA and protein synthesis and was dependent on the stage of differentiation of the cells. The maximum induction was observed around confluence (7-day-old cells), in pre- and post-confluent cells the 5'D activity was significantly less induced. The transient responsiveness of brown fat-cells to the stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…The 4 h effects of CGP-12177 were abolished by propranolol but not by prazosin, thus con®rming that beta-receptors were mostly or solely involved in the in vivo activation of 5 H -DII. These results correlate with those obtained in isolated brown adipocytes in vitro by Pavelka et al (24) and Hernandez & Obrego Ân (25). In rats injected with NE, however, prazosin ± and to a lesser extent propranolol ± blocked the NE effect, thereby suggesting that the natural agonist activated 5 H -DII in vivo via alpha-1-receptors and to a lesser extent through beta-receptors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The 4 h effects of CGP-12177 were abolished by propranolol but not by prazosin, thus con®rming that beta-receptors were mostly or solely involved in the in vivo activation of 5 H -DII. These results correlate with those obtained in isolated brown adipocytes in vitro by Pavelka et al (24) and Hernandez & Obrego Ân (25). In rats injected with NE, however, prazosin ± and to a lesser extent propranolol ± blocked the NE effect, thereby suggesting that the natural agonist activated 5 H -DII in vivo via alpha-1-receptors and to a lesser extent through beta-receptors.…”
Section: Discussionsupporting
confidence: 82%
“…The alpha-1-receptor appeared to potentiate the ability of cAMP to stimulate thermogenesis synergistically with the beta-3-receptor. A synergism between beta-and alpha-1-receptors in the stimulation of 5 H -DII activity was observed in isolated adipocytes (9) although other in vitro studies (24,25) conditions. The present data indicate that the in vivo administration of CGP-12177 can activate BAT 5 H -DII via beta-receptors without a signi®cant participation of alpha-1-receptors.…”
Section: Discussionmentioning
confidence: 99%
“…D2 is stimulated adrenergically in floating adipocytes (32), and a synergy between the ␤-and ␣ 1 -adrenergic pathways was found (38), the adrenergic stimulation of D2 being mostly ␤-adrenergic in mouse brown adipocytes (35). We have shown that T 3 is an absolute requirement for the adrenergic stimulation of D2 and amplifies this response (19).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, BAT D2 activity is upregulated by insulin (46), as shown after insulin injection, or in diabetic rats, as well as in floating rat brown adipocytes (29). In these cells, D2 activity is stimulated by adrenergic agents, and a synergy between ␣ 1 -and ␤-adrenergic pathways has been described (32,38), whereas in cultures of mouse brown adipocytes the main pathway is ␤-adrenergic (35).…”
mentioning
confidence: 93%
See 1 more Smart Citation